Meta-Analysis: Effects of Computer Skill and Management Support on Readiness to Use Electronic Medical Record in Health Workers - Delfita, Tria Fora; Murti, Bhisma; Setiyadi, Noor Alis; Tamtomo, Didik Gunawan; Novika, Revi Gama Hatta (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2025)
Background: Electronic Medical Record (EMR) is an information technology that has proven its benefits in improving service quality. This study aims to analyze the effect of computer skills and management support on health workers' willingness to use EMR. Subjects and Method: This research is a systematic review and meta-analysis study using the PRISMA diagram and PICO model. Population: health workers, Intervention: computer skills and management support, Comparison: low computer skills and no management support, Outcome: willingness to use EMR. The articles used came from Google Scholar, Pubmed, and Elsevier which were published from 2013 - 2023. The keywords used in the search were (computer skills OR Management support) AND (“willingness to use” OR “willingness to utilize” OR “readiness to implement”) AND (EMR OR electronic medical record) AND “odds ratio” AND “cross-sectional study” AND (“health personnel” OR “health workers” OR “health professionals”). The inclusion criteria for this study were full paper articles with cross-sectional studies. The analysis used was multivariate with adjusted Odds Ratio. Eligible articles were analyzed using the Revman 5.3 application. Results: Meta-analysis was conducted on 11 articles with a cross-sectional research design. Health workers who have high computer skills were 2.62 times more likely to use EMR than health workers who have low computer skills (aOR= 2.62; 95% CI= 1.92 to 3.57; p= 0.050). Health workers who received Management support were 1.87 times more likely to use EMR than health workers who did not have Management support (aOR= 1.87; 95% CI= 1.40 to 2.51; p= 0.030). Conclusion: Computer skills and management support influence the willingness to use EMR among health workers.